Effect of isoflavone consumptions on the recurrence and survival rate among breast cancer patients: an evidence-based case report - Meilianawati Meilianawati; Nurul Ratna Mutu Manikam (World Nutrition Journal, 2020)
Background: isoflavones possess both anti-estrogenic and estrogenic-like properties. Tempeh is a traditional dish from Indonesia which rich in isoflavone content. It remains controversial whether women diagnosed with breast cancer should be advised to avoid or increase the intake of food products that contain isoflavone to improve survival.Objective: to identify the association between post-diagnosis isoflavone food consumption with the recurrence and survival rate among women with breast cancer. Methods: the search was conducted with advanced searching on PubMed, Cochrane, Scopus, and ProQuest according to the clinical question. The screening of title and abstract using inclusion and exclusion criteria, filtering double, and reading full text led to six useful articles. The selected studies were critically appraised for validity, importance, and applicability.Results: five prospective cohort studies and one meta-analysis were found with comparable validity. Women at the high level of isoflavone intake (>10 mg/day) had a significant reduction in the risk of recurrence and mortality of breast cancer.Conclusion: isoflavone food intake is associated with better survival, low recurrence, and low mortality among breast cancer patients.